Revival of associating liver partition and portal vein ligation for staged hepatectomy for perihilar cholangiocarcinoma: An international multicenter study with promising outcomes - Balci, Deniz; Nadalin, Silvio; Mehrabi, Arianeb; Alikhanov, Ruslan; Fernandes, Eduardo S. M.; Di Benedetto, Fabrizio; Hernandez-Alejandro, Roberto; Björnsson, Bergthor; Efanov, Mikhail; Capobianco, Ivan; Clavien, Pierre-Alain; Kirimker, Elvan Onur; et al. (Surgery, 2023)
Associating liver partition and portal vein ligation for staged hepatectomy for perihilar cholangiocarcinoma has been considered to be contraindicated due to the initial poor results. Given the recent reports of improved outcomes, we aimed to collect the recent experiences of different centers performing associating liver partition and portal vein ligation for staged hepatectomy for perihilar cholangiocarcinoma to analyze factors related to improved outcomes.
Gesehen am 21.11.2023